Zolian Zoology: 'L'amour des bêtes' and (Human-) Animal (-Machine) Ethics. (2nd January 2021) - Robison, Christopher
ABSTRACT: A genuine investment in animal ethics pervades Emile Zola's literary production at all stages of his career, occupying a central yet often overlooked space in his moral and aesthetic thought. Situating Zola's interest in animality alongside his engagement with the life sciences of his day, the present paper examines the parameters of Zola's animal ethics as manifested in his article 'L'amour des bêtes' ( Le Figaro, March 24, 1896), with an eye towards their elaboration in selections from his broader oeuvre. Central to Zola's animal ethics, I argue, is a materialist Human-Animal-Machine trichotomy whose three parts he treats as radically interchangeable.